Bonding in Microsystem Technology - Dziuban, Jan A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
Bonding in Microsystem Technology starts with descriptions of terminology, kinds of microsystems and market analysis. Followed by the presentation of mechanisms of wet etching, set of process parameters, description of micromachining methods, examples of procedures, process flow-charts and applications of basic micromechanical structures in microsystems are shown. Next, high-temperature, low temperature and room-temperature bonding and their applications in microsystem technology are presented. The following part of the book contains the detailed description of anodic bonding, starting from analysis of properties of glasses suitable for anodic bonding, and discussion of the nature of the process. Next all types of anodic bonding and sealing procedures used in microsystem technology are presented. This part of the book finishes with examples of applications of anodic bonding in microsystem technology taken from the literature but mainly based on the author’s personal experience.
Some Remarks on Microsystem Systematics and Development -- Deep, Three-Dimensional Silicon Micromachining -- Bonding -- Classification of Bonding and Closing Remarks.
Keywords: Mechanics; Mechanics, Applied; Engineering; Optical materials; Electronic materials; Electronics; Microelectronics; Manufactures; Solid Mechanics; Engineering, general; Optical and Electronic Materials; Electronics and Microelectronics, Instrumentation; Manufacturing, Machines, Tools, Processes